Thank You's (Symphony in the Flint Hills, 2015)
Acknowledgements and thanks for all those involved in the Symphony in the Flint hills and the production of the Field Journal.
Keywords: sponsors; patrons; grassroots; The Westar Energy Team; Volunteers; Advisors; Staff; Symphony in the Flint Hills; Home on the Range; Thank You